Learning Evaluation: Characteristics of Excellent Assessment - Falaqi Muhamad Rizal; Munandar Khalilul Fathir; Husein, Muhammad Ghafiqi; Ramadhan, Muhamad Said; Zafarani, Reihan Arvie; Aminoor, Afgatan Syadan; Amrullah, Muhammad Luthf (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: The aim of this research is to explain the learning evaluation process which focuses on the characteristics of excellent assessment. Evaluation has an important role in learning outcomes and one way to obtain excellent test items is to test the validity of the test items. One way to find out student learning outcomes is to carry out learning evaluations. In learning evaluation there is an assessment process which has an important role in measuring student abilities. So it is important for a teacher to know the characteristics of excellent assessment. If the learning evaluation is carried out well, the results of the evaluation are used to improve the learning curriculum used. Methodology: Qualitative research methods and library research types of research are used to determine the characteristics of excellent assessment. The collected data is then analyzed using several stages of data analysis, and then data validity is carried out to determine the validity of the data. Findings: This research shows that the characteristics of an excellent assessment are: 1) Validity, the tools used in the assessment process are valid. 2) Consistency, when the assessment is carried out with various assessment objects, the assessment results do not differ too much and are stable. 3) Objectivity, meaning there is no subjectivity factor in carrying out the assessment. 4) Ease of Application, both ease of implementation and ease of inspection. 5) Economical, doesn’t cost a lot of money, energy or time. Implications/Novel Contribution: The seriousness of educators in carrying out the assessment process must be considered so that the objectives of learning evaluation are achieved. So, with the successful implementation of the assessment, student learning goals can be achieved.